Quantitative Anatomical Characteristics of the Leaf Blades of the Several Species of Crataegus L. - V. A. Sagaradze; E. Yu. Babaeva; E. I. Kalenikova; N. A. Trusov; E. V. Peshchanskaya (Разработка и регистрация лекарственных средств, 2021)
Introduction. The Crataegus L. (Hawthorn) is a common herb in numerous Pharmacopoeias. The State Pharmacopoeia of the Russian Federation provides hawthorn fruits and flowers for medical utilization. With that, the literature data confirms the medical utility of hawthorn leaves since the “leaves” and the “flowers with leaves” have pharmacopoeial status worldwide. Therefore, those are considered as prospective forms of Crataegus raw material for Russian pharmaceutical production. However, most species remain poorly pharmacognostically investigated regarding the quantitative microscopic characteristics (the sizes of stomatal apparatus (SA) and epidermal leaf blade (LB) trichomes), which could be substantial for establishing the authenticity of the raw material.Aim. Examine epidermal anatomy of Crataegus spp. Leaf blades (LBs) and perform a comparative study of several quantitative diagnostic features of LBs of hawthorn plants from the sect. Sanguineae and the sect. Crataegus, growing in diverse regions of the Russian Federation.Materials and methods. Samples of hawthorn leaves (C. sanguinea, C. maximowiczii, C. dahurica, C. rhipidophylla, C. monogyna and C. pallasii) were collected in natural habitats in Western Siberia (Kemerovo) and in arboretums of Botanical Gardens (Moscow, Stavropol). Measurements of anatomical structures were carried out using a light microscope accompanied by an ocular micrometre.Results and discussion. The LB surface phenotypic diversity within hawthorn species and sections was studied. The LBs were described in terms of meterages (longitude and width) of SA, meterages and shape of sedentary multicellular leaf teeth glands. The peculiarities of pubescence and the sizes of simple unicellular non-glandular trichomes were also observed.Conclusion. The results of quantitative anatomical examination provided the characteristic features determining these elements at the species and section levels. Thus, it may facilitate authentication and quality control of whole or ground Crataegus medicinal raw material.